Analysis of the Implementation of Convergence in Reducing Stunting in Meranti Islands Regency - Siti Rukijah*; Mitra Mitra; Novita Rany (Riwayat: Educational Journal of History and Humanities, 2023)
Implementation of convergence in an integrated stunting prevention program is already a national policy specified in Presidential Decree Number 72 of 2021 concerning Accelerating the Reduction of Stunting. Meranti Regency as a Regency in Riau province which is the location of the focus of stunting has not implemented efforts to reduce stunting in accordance with the convergence action guidelines. The coverage of the stunting prevalence rate in Meranti Islands Regency in 2022 is 17.5%. The research objective was to obtain in-depth information about the implementation of the stunting reduction program through convergence action in Meranti Islands Regency in 2023. This type of research is qualitative with a case study approach. There were 9 informants consisting of several related stakeholders, namely the Regional Apparatus Organization (OPD) as the holder and implementer of the stunting program. The triangulation used is the triangulation of sources, methods and data. The results of the research show that support policies in an effort to reduce stunting cases refer to Presidential Regulation Number 72 of 2021 and Meranti District Regent Regulations, the quantity of human resources, facilities and infrastructure and funding is still lacking. Planning, convergence implementation, monitoring and evaluation of stunting reduction have been carried out in accordance with Presidential Regulation Number 72 of 2021 and there are still obstacles in planning and implementing activities. The implementation of stunting reduction convergence in Meranti Islands Regency was able to reduce the stunting rate in 2019-2022 from 25.10% to 17. 5% or almost 2.5% annually. Bappeda and the head of the health office should work together to carry out ongoing advocacy to the local government and DPRD to obtain policy and financial support in efforts to prevent stunting in Meranti District